2009
DOI: 10.4314/afrrev.v3i2.43636
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Sustained Environmental Resource Crisis in the Niger Delta Region of Nigeria: A Theoretical Periscope

Abstract: The Niger Delta region of Nigeria witnessed a remarkable upsurge in environmental resource crisis as a result of the presence of oil multinationals in the region. The mass media flash before the public a vivid and multi varied images of violent behaviour that characterized social interactions in the region. The youths in the Niger Delta whose occupational aspirations are blocked due to persistent hydrocarbon extraction in their region resorted to violent behaviour as a rational response to the monumental depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Enemugwem (2009) in the study of how oil pollution damaged human ecology in eastern Obolo (Andoni LGA) in Rivers State observed that oil pollution had not only degraded the human values but had adverse effects on the flora and fauna, traditional economies and social practices of the people in the area, increased poverty, food contamination and lack of security of human life. This view was supported by Ogege and Ewhrudjakpor (2009) who said that the Niger Delta region of Nigeria had witnessed a remarkable up surge in environmental resource crisis as a result of the presence of oil multinationals in the region.…”
Section: Indexed African Journals Online: Wwwajolinfomentioning
confidence: 97%
“…Enemugwem (2009) in the study of how oil pollution damaged human ecology in eastern Obolo (Andoni LGA) in Rivers State observed that oil pollution had not only degraded the human values but had adverse effects on the flora and fauna, traditional economies and social practices of the people in the area, increased poverty, food contamination and lack of security of human life. This view was supported by Ogege and Ewhrudjakpor (2009) who said that the Niger Delta region of Nigeria had witnessed a remarkable up surge in environmental resource crisis as a result of the presence of oil multinationals in the region.…”
Section: Indexed African Journals Online: Wwwajolinfomentioning
confidence: 97%